The determinants of local employment dynamics in Western Germany - Fuchs, Michaela (Nürnberg, 2009)
"This paper studies the impact of the local industrial structure on employment dynamics in Western Germany. Following an approach of Combes/Magnac/Robin (2004) for France, local employment growth is decomposed into internal growth resulting from employment changes in existing plants and into external growth determined by employment decisions of newly established plants. The dynamics of both components are estimated simultaneously, taking explicitly into account the timing of the impact of specialization, diversity, and competition in a region. The analysis is conducted for 24 sectors in the West German labor market regions from 1993 to 2002. Estimation results emphasize the positive influence of diversity on both internal and external employment growth, whereas there is no clear result on specialization. A high degree of competition fosters external employment, but is detrimental to internal employment. Dynamic panel regressions show that static externalities dominate. Importantly, the impact of the local industrial structure on employment dynamics does not differ between small and larger plants, nor are there fundamental differences between Western Germany and France."